PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA PENCUCIAN UANG PERSPEKTIF HUKUM ISLAM - Ais Surasa (Balai Diklat Keagamaan Bandung, 2020)
This research aims to find out the conditions of corporate criminal liability in money laundering offences based on Islamic law perspective. This research uses library research methods. The results concluded that corporate criminal liability conditions are stipulated in Article 6 of Law No. 08 year 2010, which contains that a person with money laundering will be 4 years or more in prisoned. Islamic law states that one who commits it, will be punished in return towards the actions of “jarimah” perpetrators (as the elements fulfilled). Thus, the criminal liability is a person who can experience a shift and accept the concept of harm through determining corporate’s liability. It is because the will-have impact is greater than any crimes executed by individuals. As for the sanctions against corporations which committed money laundering are ta'zir (punishments). Keywords: Corporate Criminal Liability; Money Laundering; Islamic Law